Information Metamaterial Systems - Cui, Tie Jun; Li, Lianlin; Liu, Shuo; Ma, Qian; Zhang, Lei; Wan, Xiang; Jiang, Wei Xiang; Cheng, Qiang (iScience, 2020)
Metamaterials have great capabilities and flexibilities in controlling electromagnetic (EM) waves because their subwavelength meta-atoms can be designed and tailored in desired ways. However, once the structure-only metamaterials (i.e., passive metamaterials) are fabricated, their functions will be fixed. To control the EM waves dynamically, active devices are integrated into the meta-atoms, yielding active metamaterials. Traditionally, the active metamaterials include tunable metamaterials and reconfigurable metamaterials, which have either small-range tunability or a few numbers of reconfigurability. Recently, a special kind of active metamaterials, digital coding and programmable metamaterials, have been presented, which can realize a large number of distinct functionalities and switch them in real time with the aid of field programmable gate array (FPGA). More importantly, the digital coding representations of metamaterials make it possible to bridge the digital world and physical world using the metamaterial platform and make the metamaterials process digital information directly, resulting in information metamaterials. In this review article, we firstly introduce the evolution of metamaterials and then present the concepts and basic principles of digital coding metamaterials and information metamaterials. With more details, we discuss a series of information metamaterial systems, including the programmable metamaterial systems, software metamaterial systems, intelligent metamaterial systems, and space-time-coding metamaterial systems. Finally, we introduce the current progress and predict the future trends of information metamaterials. [Display omitted] Electromagnetic Waves; Information Systems; Metamaterials